Differentiate y=(x^2 + 2x)cos(3x)

Here we need to use the product rule in order to differentiate as we have two functions involved that are being multiplied together. Therefore we use the formula:dy/dx = u dv/dx + v du/dxFirst let u=(x^2 + 2x) and v=cos(3x)Therefore du/dx = 2x + 2 and dv/dx= -3sin(3x) (using chain rule)Next plug the values into the formula to get:dy/dx = (x^2 + 2x)(-3sin(3x)) + cos(3x)(2x + 2)

Answered by Katie B. Maths tutor

3118 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Given x=Sqrt(3)sin(2t) and y=4cos^2(t), where 0<t<pi. Show that dy/dx = kSqrt(3)tan(2t).


Find the binomial expansion of (4-8x)^(-3/2) in ascending powers of x, up to and including the term in x^3. Give each coefficient as a fraction in its simplest form. For what range of x is a binomial expansion valid?


Integral of a compound equation (or otherwise finding the area under a graph): f(x) = 10x*(x^(0.5) - 2)


How do I use the chain rule for differentiation?


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences